Crocus sativus L. Extract and Its Constituents: Chemistry, Pharmacology and Therapeutic Potential - Pitsikas, Nikolaos; Dimas, Konstantinos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Natural products or organic compounds isolated from natural sources as primary or secondary metabolites have inspired numerous drugs. It is not an overstatement that the majority of medicines in clinics, even in the 21st century, have been derived from natural resources despite the decline of industry research into natural products due to a variety of drawbacks. Saffron crocus, considered to be the most valuable spice by weight, and its bioactive constituents, have been studied for the treatment of a wide range of pathologies, including neuropsychiatric and neurodegenerative disorders, cancer, diabetes, and even cardiovascular diseases. In this book on the chemistry, pharmacology, and therapeutic potential of Crocus sativus L. extract and its constituents, we aimed to assess new advances in the understanding of the therapeutic action of saffron and its constituents in targeting different pathologies. In this context, eight original research articles covering recent advances in the therapeutic actions of saffron and its ingredients in different diseases are reported. Two studies reporting novel methods regarding the bioanalysis of saffron extracts have been included. The collection is completed with two very interesting reviews reporting advances in the fields of schizophrenia and cancer. In conclusion, in this book, we are delighted to have received several contributions that we hope will provide new and interesting information for the scientific community on the chemistry, pharmacology, and therapeutic potential of Crocus sativus L. extract and its constituents.